Development and validation of two bioanalysis methods for the determination of etimicin in human serum and urine by liquid chromatography-tandem mass spectrometry: Applications to a human pharmacokinetic and breakpoint study - Cui, Xinge; Zheng, Xin; Ren, Jianwei; Liu, Hongzhong; Jia, Yuan; Wu, Aiguo; Han, Xiaohong (Frontiers in Pharmacology, 2023)
Etimicin is a fourth-generation aminoglycoside antibiotic. It has potent activity and low toxicity when employed for the treatment of Gram-negative and Gram-positive bacterial infections. The pharmacokinetics of etimicin in humans have not been elucidated completely. Two liquid chromatography-tandem mass spectrometry (LC-MS/MS) bioanalytical methods, without the use of any ion-pairing reagents, were developed and validated for the quantification of etimicin in human samples of serum and urine. Using a deuterated reagent as the internal standard, analytes in serum and urine samples were extracted by protein precipitation and dilution before LC-MS/MS analysis, respectively. For the two methods, chromatographic separations were undertaken under isocratic elution of water–ammonia solution–acetic acid (96:3.6:0.2, v/v/v) and methanol at 50%:50% and a flow rate of 0.35 mL/min within 5 min. A Waters XTerra MS C18 column (2.1×150 mm, 3.5 μm) and a column temperature of 40 °C were chosen. A Sciex Qtrap 5500 mass spectrometer equipped with an electrospray ion source was used in both methods under multiple-reaction monitoring in positive-ion mode. The two methods showed good linearity, accuracy, and precision with high recovery and a minimal matrix effect in the range of 50.0–20000 ng/mL for serum samples and 50.0–10000 ng/mL for urine samples, respectively. Carry-over effects were not observed. Etimicin remained stable in human samples of serum or urine under the storage, preparation, and analytical conditions of the two methods. These two simple and reliable methods were applied successfully to a dose-escalation, phase I clinical trial of etimicin in Chinese healthy volunteers after intravenous administration of single and multiple doses. Based on these two methods we ascertained, for the first time, the comprehensive pharmacokinetics of etimicin in humans, which will be used for the exploration of the breakpoint research further.